Substandard and Falsified Medicines in Myanmar - Mirai Sakuda; Naoko Yoshida; Takashi Takaoka; Tomoko Sanada; Mohammad Sofiqur Rahman; Tsuyoshi Tanimoto; Theingi Zin; Kazuko Kimura; Hirohito Tsuboi (MDPI AG, 2020)
Background: substandard and falsified medicines (SFMs) are a threat to public health. The availability of SFMs in Myanmar was reported by the World Health Organization (WHO) in 1999, but there have been few systematic surveys on falsified medicines in Myanmar since then. The aim of this study is to examine the extent of SFMs for sale in Myanmar. Methods: target medicines were tablets of candesartan, metformin, and pioglitazone, and infusions of ciprofloxacin and levofloxacin. Samples were collected from hospitals, pharmacies, and wholesalers located in the Mandalay region in 2015. We carried out observation testing, authenticity investigation, and quality testing to search for SFMs, and analyzed the relationship between SFMs and the price and store type. Results: There were no falsified medicines found in the authenticity check, though there remained a problem due to low response rates from manufacturers and regulatory authorities. In the quality test, some tablets of metformin and pioglitazone made in India failed the dissolution test. Conclusions: although no serious problems were found, some substandard medicines were detected. Regular surveys to monitor SFMs are therefore recommended, together with further regulatory guidance to improve conditions in all medicine manufacturers, distributors, and pharmacies.